Inverter Development as A Boost Converter for DC Microgrid - Budiyanto Budiyanto; Rudy Setiabudy; Eko Adhi Setiawan; Aditya Kurniawan (Universitas Ahmad Dahlan, 2013)
DC boost converter is an essensial equipment in the system of DC microgrid which has a function as step up voltage. In making a boost converter equipment of power generation, it often encounters a problem within especially in designing of switching transformer, so that it is need a long development time and high development cost. In order to solve this problem, in this research it has been made a inverter development as boost converter which has been done by simulation and experiment. The simulation results show that for an input voltage 10-14 Vdc yields voltage 254 Vdc, while by testing for an input voltage 10-14 Vdc yields voltage 253 Vdc. Either simulation or test result show that voltage can be applied in the system of dc micro grid for the need of load based switch mode power supply /SMPS.